The Character of Physical Education Teachers and Mass Media on Knowledge and Student Attitudes about HIV/AIDS (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
More than 50% of AIDS cases occur at the age of adolescence to adulthood. Therefore early knowledge should be given to prevent HIV/AIDS. The objectives of this study were to know the effect of roles of physical education teacher toward the students knowledge, to know the roles of mass media to students knowledge, to know the roles of physical education teacher toward students’ attitude, the roles of mass media to students’ attitude, students’ knowledge to students’ attitude in understanding prevention and danger of HIV/AIDS in Grobogan District. The population of this study was the whole students in Grade, i.e. 11 State Senior High Schools in Grobogan District or 3,397 students. The instruments used to collect data are questionnaires. The technique of data analysis that used was related to respondent description and description of research variables. (1) The roles of physical education teachers had no significant effect toward the students’ knowledge, (2) The roles of mass media had positive and significant effect toward students’ knowledge, (3) The roles of physical education teachers had positive and significant effect toward students’ attitude, (4) The role of the mass media proved to have no significant effect toward students' attitudes, (5) Students’ knowledge had positive and significant effect e toward students’ attitude; variable of students’ knowledge could not mediate the effect of physical education teacher toward students’ attitude on HIV/AIDS; and (7) Students’ knowledge could mediate the effect of physical education teacher toward students’ attitude on HIV/AIDS.